2012
DOI: 10.1371/journal.pone.0036907
|View full text |Cite
|
Sign up to set email alerts
|

Modified Laminar Bone in Ampelosaurus atacis and Other Titanosaurs (Sauropoda): Implications for Life History and Physiology

Abstract: BackgroundLong bone histology of the most derived Sauropoda, the Titanosauria suggests that titanosaurian long bone histology differs from the uniform bone histology of basal Sauropoda. Here we describe the long bone histology of the titanosaur Ampelosaurus atacis and compare it to that of basal neosauropods and other titanosaurs to clarify if a special titanosaur bone histology exists.Methodology/Principal Findings Ampelosaurus retains the laminar vascular organization of basal Sauropoda, but throughout most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 29 publications
0
59
0
2
Order By: Relevance
“…A similar pattern is observed in the dorsal ribs, which are extensively remodelled but retain primary fibrolamellar bone tissue towards the periosteal surface. Recent analyses5556 have suggested that titanosaurs may have developed extensively remodelled tissues after reaching sexual maturity but prior to attaining their maximum size. Thus, the presence of unremodelled fibrolamellar bone in the outer cortex of the MPM-PV 1156 humerus suggests that this massive Dreadnoughtus individual was still growing at the time of its death.…”
Section: Discussionmentioning
confidence: 99%
“…A similar pattern is observed in the dorsal ribs, which are extensively remodelled but retain primary fibrolamellar bone tissue towards the periosteal surface. Recent analyses5556 have suggested that titanosaurs may have developed extensively remodelled tissues after reaching sexual maturity but prior to attaining their maximum size. Thus, the presence of unremodelled fibrolamellar bone in the outer cortex of the MPM-PV 1156 humerus suggests that this massive Dreadnoughtus individual was still growing at the time of its death.…”
Section: Discussionmentioning
confidence: 99%
“…parallel‐fibred bone including lamellar; see below) from rapidly growing, poorly organized tissue (i.e. woven bone) (Sander, ; Padian, Horner & Ricqlès, ; Ricqlès et al ., ; Chinsamy‐Turan, ; Curry Rogers & Erickson, ; Cambra‐Moo et al ., ; Horner et al ., ; Scheyer, Klein & Sander, ; Stein et al ., ; Sander et al ., ; Klein et al ., ; Prondvai et al ., ; Huttenlocker, Woodward & Hall, ).…”
Section: Controversial Issues Related To the Application Of The Tradimentioning
confidence: 99%
“…These include the species Ampelosaurus atacis (Le Loeuff, 1995), Lirainosaurus astibiae (Sanz, Powell, Le Loeuff, Martínez, & Pereda-Suberbiola, 1999) and Atsinganosaurus velaucencis (Garcia et al, 2010) as well as three new titanosaur species pending definitive description. Among the latter, a new titanosaurid taxon is identified at the localities of Massecaps (Klein et al, 2012), Lo Hueco and Fox-Amphoux-M etisson (Díez Díaz, Ortega, Sanz, 2014;Díez Díaz, Tortosa, & Le Loeuff, 2013), and two new and distinct taxa thought to be present in the latter localities (Díez Díaz, 2013). In the post-turnover associations (formerly the "late Maastrichtian assemblages") at least four titanosaurid taxa have been recognized.…”
Section: Taxonomic Diversity: Clade-specific Patternsmentioning
confidence: 99%